Winged Beans Extract-Doped-Hybrid Composite Sol-Gel Coating For Corrosion Resistance Of Carbon Steel In 0.5 M Hydrochloric Acid - Zakaria, Farah Athena (2022)
The present work focuses on the extraction of winged bean (WB) with different polarity of solvent for the application of corrosion inhibitor to reduce the corrosivity of carbon steel in 0.5 M HCl medium. It was revealed that winged bean water extract (WBW) had the highest percentage yield, followed by winged bean ethanol (WBE), methanol (WBM), and hexane (WBH) extract. Further characterization using complementary analyses disclosed the values of TPC, TFC and FRAP in trend such WBW (TPC: 117.40; TFC: 54.65) > WBE (TPC: 98.52; TFC: 52.67) > WBM (TPC: 82.64; TFC: 37.29) > WBH (TPC: 23.80; TFC: 17.59). A series of phytochemical screening and HPLC analysis qualitatively show the presence of phenolic compounds like gallic acid and ferulic acid which then quantified. FTIR spectra of WB extract discovered the presence of functional groups that characterize good corrosion inhibitors. The inhibition action of WB extracts studied using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PD), and electrochemical noise measurement (ENM) techniques revealed that WBW and WBE inhibition efficiencies (IE) from the three different techniques at 1000 ppm were beyond 80%. Overall data obtained suggested the Langmuir adsorption isotherm and physisorption mechanism with ΔGads ≤ -20 kJ mol-1, best described the inhibitory process of both WB extracts. Further application of WB extracts as additive in sol-gel coating results in the formation of Fe-Si-O from the characterization through FTIR-ATR and SEM-EDX with good hydrophobicity with wetting angle of > 100°.